Impact of Educational Intervention on Mothers' Knowledge and Home Management Practices of Childhood Diarrhea in Under-Five Children (Journal of Neonatal, Infant and Child Health Nursing, 2026)
Childhood diarrhea remains a leading cause of preventable morbidity and mortality among children under the age of five globally, particularly in low- and middle-income countries (LMICs). Despite the availability of highly effective, low-cost interventions such as Oral Rehydration Salts (ORS), zinc supplementation, and continued feeding, sub-optimal maternal knowledge and inadequate home management practices continue to fuel poor clinical outcomes. This comprehensive narrative review evaluates the transformative role of structured educational interventions in enhancing maternal comprehension and improving localized home care practices. Globally, diarrheal diseases account for an estimated 9% of all deaths in under-five children, translating to over 480,000 child deaths annually. The etiology of these illnesses is deeply intertwined with a web of biological, environmental, socioeconomic, nutritional, and behavioural risk factors. This paper systematically explores these determinants, emphasizing how geographical variations and structural inequities influence disease distribution.Mothers are universally recognized as the primary caregivers and first line of defence during acute childhood illness. However, empirical literature consistently highlights substantial gaps in their baseline knowledge regarding the recognition of early dehydration signs, appropriate fluid volume administration, the physiological significance of zinc therapy, and the critical importance of maintaining nutritional intake during diarrheal episodes. This review examines a variety of educational modalities—including community-based peer counselling, hospital-based instructional programs, traditional health literacy campaigns, and contemporary digital health/mobile health (mHealth) frameworks.
Keywords: Childhood Diarrhea; Educational Intervention; Home Management; Maternal Knowledge; Oral Rehydration Therapy; Public Health Nursing; Under-Five Mortality